1990
DOI: 10.1111/j.1151-2916.1990.tb07613.x
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Fracture Toughness of Ceramic Materials: Effects of Dynamic Loading and Elevated Temperatures

Abstract: Experimental methods are presented for the determination of fracture initiation toughness of ceramics and ceramic composites in pure tension under quasi-static and dynamic loading conditions over a range of temperature spanning 20" to 1300°C. Circumferentially notched and cyclic fatigue precracked rods of a variety of ceramic materials were subjected to quasi-static tensile fracture (rate of stress intensity factor loading, K I = 0.1 MPa. m'". s -I ) in an electroservohydraulic test machine and to dynamic tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 16 publications
4
26
2
Order By: Relevance
“…It is concluded that the interaction between cracks and the microstructure is independent of strain rate in the investigated regions. Brokenbough et al [36] and Suresh et al [37] observed, nevertheless, an increase in fracture toughness with strain rate in ceramics K ID aK IC 1X1±1X4X Some monolithic ceramics (such as Al 2 O 3 and Si 3 N 4 ) contain intergranular glassy phases. The glassy phase can signi®cantly in¯uence the properties of the ceramic.…”
mentioning
confidence: 99%
“…It is concluded that the interaction between cracks and the microstructure is independent of strain rate in the investigated regions. Brokenbough et al [36] and Suresh et al [37] observed, nevertheless, an increase in fracture toughness with strain rate in ceramics K ID aK IC 1X1±1X4X Some monolithic ceramics (such as Al 2 O 3 and Si 3 N 4 ) contain intergranular glassy phases. The glassy phase can signi®cantly in¯uence the properties of the ceramic.…”
mentioning
confidence: 99%
“…In order to use the dynamic G calculation for axisymmetric solids and apply the iterative scheme in a meaningful analysis, we have chosen to simulate the dynamic fracture experiment carried out by Suresh et al [8]. In their experiment, a round ceramic bar with circumferentially fatigue notched specimen was employed to determined the dynamic crack initiation toughness t(Id of various ceramics.…”
Section: Dynamic Fracture Testing Of Ceramicsmentioning
confidence: 99%
“…The record of transmitted load shows the crack initiation to occur around 14 #sec after the initial loading wave arrives at the crack region. Using the peak level of the transmitted load, the dynamic crack initiation toughness of A1203 was found to be Kid = 3.5 MPav/-m at room temperature [8]. Although the peak load was the only information needed to determined Kid, a complete transmitted load history is available from the experimental record.…”
Section: Dynamic Fracture Testing Of Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate fluctuations in dynamic stress intensity factor in relatively large three-point bend specimens of 75 mm height and 10 mm thickness and 89 mm height and 9.5 mm thick were documented in [3] and [4], respectively, but not to the extent shown in [1,2]. This superfluous reflected stress wave effects was eliminated by replacing the above two-dimensional fracture specimens with an one-dimensional specimen, such as that used by Duffy and his colleagues [5,6]. Despite its cleanness in test conditions, this split Hopkinson tensile bar test, which is loaded by explosives, requires special training and laboratory facilities.…”
mentioning
confidence: 98%